"Opinions of Eastern thinkers on child rearing" - Elmuradova Lola Tojialievna; Rakhimova Munisa (Genius Journals, 2021)
This article is about the bright ideas and opinions of Eastern thinkers, scholars, writers on the upbringing of children, their nature, their upbringing as a harmoniously developed generation. The article reflects the views of Eastern thinkers Alisher Navoi, Abu Ali ibn Sino, Abu Nasr Farobi, Mirzo Ulugbek, Nuriddin Abdurahman Jami, Yusuf Khas Khojib, Abdullah Avloni on the high moral qualities such as morality, honest work, true friendship and devotion. listed
Keywords: Moral maturity; pedagogical perspective; parents; family